PELATIHAN PENYUSUNAN RUBRIK PENILAIAN PEMBELAJARAN KOLABORATIF DAN PARTISIPATIF PADA JURUSAN SOSIOLOGI UNIVERSITAS PALANGKA RAYA - Anam, M Syaeful; Saragih, Osi Karina; Ningrum, Windi Susetyo; Batubara, Muhammad Zusanri; Atem, Atem; Irawansyah, Iman; Fauzi, M. Zainuddin Lutfi (LPPM Universitas Nusa Mandiri, 2026)
The training on developing assessment rubrics for collaborative and participatory learning at the Department of Sociology, Universitas Palangka Raya, was conducted in response to the need to enhance the quality of project- and case-based learning evaluation. The program aimed to improve lecturers’ understanding and skills in designing authentic assessment rubrics aligned with 21st-century learning principles and Key Performance Indicator (KPI) 7 for higher education institutions. The community service activity employed a participatory training method conducted through four stages, namely needs identification, material development, rubric development training, and evaluation. A total of 15 lecturers participated in the training. Data were collected through participatory observation, evaluation questionnaires, and document analysis of the rubrics produced by participants. The results indicate an increase in the average understanding score from 58.4 to 82.7, reflecting a gain of 24.3 points. A total of 83% of participants achieved a score of ≥75 on the post-test, meeting the predefined success indicator. Twelve rubric drafts were produced, of which 83% met content validity criteria based on facilitator review. The satisfaction survey showed that 85% of participants were very satisfied with the training. Overall, the program effectively enhanced lecturers’ capacity to design measurable and contextual collaborative assessment tools that support the achievement of KPI 7. Follow-up training and mentoring are recommended to ensure sustainable implementation of the rubrics in classroom practice.